Patrick Modiano i jego (nie)żydowskie genealogie - Sadkowski, Piotr (Archiwum Emigracji. Studia – Szkice – Dokumenty, 2016)
PATRICK MODIANO AND HIS (NON-)JEWISH GENEALOGIES With a few exceptions, Jewish motifs in the prose of Patrick Modiano are veiled, vague, metaphorical and connected with the wider, universal and problematic aspects of the struggle of a contemporary, lonely man with a wounded memory, uncertainty about his identity, as well as the impossibility of recovering lost time. However, the memory of the Jewish origin of his ancestors on his father’s side and the legacy of trauma of Holocaust victims and survivors are remarkably important and disturbing elements of the writer’s personality, sensitivity, and ethics. This is why the 2014 Nobel Prize winner’s work is the object of research by francophone literary scholars exploring post-Holocaust Jewish identity in the late 20th-century writing. The article analyses the Jewish motifs in Modiano’s prose, classified by many contemporary critics as a model example of autofiction.